Kombucha : technology, traceability, and health promoting. (Academic Press, 2025)
Kombucha: Technology, Traceability, and Health-Promoting Effects covers both conventional and unconventional sources for the development of kombucha analogues, along with their sensory, functional, and nutritional aspects. Topics include process conditions, their escalation and impact on the chemical composition, the biochemistry to produce scoby, and the functionality of the drinks. Regulatory aspects in different countries, as well as myths and realities of kombucha's bioactivities, are also covered. Users will find a great resource that also documents the probiotic potential of this popular drink, highlighting metabiotics, nutribiotics, and the pharmabiotics present. This book will serve as a valuable resource for researchers in food science and beverage science, especially those interested in fermentation.